Loss of Y-chromosome does not correlate with age at onset of head and neck carcinoma: a case-control study - Silva Veiga,L.C. (2012)
Loss of Y-chromosome has been correlated with older age in males. Furthermore, current evidence indicates that Y-chromosome loss also occurs in several human tumors, including head and neck carcinomas. However, the association between Y nullisomy and the occurrence of neoplasias in elderly men has not been well established. In the present study, the association between Y-chromosome loss and head and neck carcinomas was evaluated by comparison to cells from peripheral blood lymphocytes and normal mucosa of cancer-free individuals matched for age using dual-color fluorescence in situ hybridization. Twenty-one patients ranging in age from 28 to 68 years were divided into five-year groups for comparison with 16 cancer-free individuals matched for age. The medical records of all patients were examined to obtain clinical and histopathological data. None of the patients had undergone radiotherapy or chemotherapy before surgery. In all groups, the frequency of Y-chromosome loss was higher among patients than among normal reference subjects (P < 0.0001) and was not age-dependent. These data suggest that Y-chromosome loss is a tumor-specific alteration not associated with advanced age in head and neck carcinomas.